Analisis Pengaruh Tingkat Pendidikan Dan Kompensasi Terhadap Produktivitas Kerja Pegawai Kantor Dinas Pasar Kota Padang - Gustina, Leni; Rahmi Aswin, Ullya; Sari, Fitrah (CV. ITTC INDONESIA, 2022)
This study aims to examine and analyze the effect of education level and compensation on work productivity of employees of the Padang City Market Service Office. The independent variables used are education level (X1) and compensation (X2). The dependent variable is employee work productivity (Y). The type of research methodology used is the causative method. The data used are primary and secondary data. Primary data was obtained by interviewing a sample of 97 Padang City Market Service employees. The analysis tool used is Multiple Linear Regression with the SPSS version 19.0 program. The results of the study show that the first hypothesis (H1) can be accepted. It can be seen that the tcount value for this variable is 3.137. Meanwhile the value in the 5% distribution table is 2.376. Then tcount (3.137) > ttable (2.376). This means that the education level variable (X1) has a positive influence. This is also reinforced by the significance value (0.004 <0.050) meaning that the education level variable (X1) has a positive and significant effect on the work productivity of Padang City Market Service employees. Whereas the second hypothesis (H2) is also accepted, seen in the tcount value for this variable of 5.020. Meanwhile the value in the 5% distribution table is 2.376. Then tcount (5.020) > ttable (2.376). This means that the compensation variable (X2) has a positive influence. This is also reinforced by the significance value (0.000 <0.050) meaning that the compensation variable (X2) has a positive and significant effect on the work productivity of Padang City Market Service employees. For the third hypothesis (H3) it is also accepted that Fcount is 15.535, while the results of Ftable in the distribution table with an error rate of 5% are 3.44. This means Fcount > Ftable (15.535 > 3.44). These calculations show that the variable level of education (X1) and compensation (X2) together have a positive and significant influence on employee productivity variables (Y).